(3GdjJjeI GdZQhjI hGdJMaI GdfLajI aj GdHbYI GdeHGQcI GdRcjIs - (3GdHQGbj, MShf, MSjf Hf CMeO Hf GdMSjf Hf ESeGYjd GdMSfj, J (B1332 (3g`s ((3GdeDdas)
(3ChdgG (B:s
(3hef dCLdg NdbJ GdNdGFb hHGfJ Hg GdMbGFb (B... (3Cbhd (B..(3Efj deG QCjJ cJH GdCNHGQ hfXQJ Edi GdSjQ hGdBKGQ HYhf Gddg Gdedc GdZaGQ ade CYKQ Ydi cJGH eSJbd eJVef daVd (B... (3GdfLa GdCTQa heG GYO Gddg ajgG dCgdgG ef GdTQa Shi cJH GdeRGQGJ hcJH GdCNHGQ ajgG HYV GdETGQGs
(3BNQgG (B:s
... (3dh de CLO SGMdg ddOgQ efJgjG dbdJ CTHgg aj GdfGFd GdZeQ (B... (3bO QeJ CWjH aj eOMj dSDOO dcf caGfj CeQj eMce GdShQ (B.(3GfJgis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\233s
(3GdPQjYI (B25 - 169 (84)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdLZQGajG hGdHdOGfs